Enhancing copper and lead bioaccumulation in rapeseed by adding hemp shives as soil natural amendments - Tanase, Corneliu; Volf, Irina; Popa, Valentin I. (Journal of Environmental Engineering and Landscape Management, 2014)
The current study reveals the results of a phytoremediation process applied to a multi metal contaminated soil, located in close proximity to an energy power plant. Phytoremediation process was studied using the rapeseed cultivation, both in the presence and absence of hemp shives, considered as potential natural soil amendments. The physiological responses of the rapeseed plants, such as variations in length and accumulation of biomass, as well as the content of assimilating pigments were investigated. The concentrations of Cu (II) and Pb (II) ions have also been determined in soil and plants aiming at locating the metal ions in different organs of the plants. By using hemp shives as amendments, bioaccumulation of copper and lead ions in plant increases. The plants cultivated in the presence of high amounts of heavy metal ions have been characterized by an inhibition of growth and development that consisted in decrease of root and stem lengths, as well in the amount of biomass accumulated in different vegetative organs.